O Cinematógrafo E O Fora: Conexões Entre Robert Bresson E Gilles Deleuze - Garcia, Renata Siramizu [UNIFESP] (2017)
The aim of this research is to examine the theory of the cinematography by Robert Bresson, through Gilles Deleuze’s writings on cinema. There are four main movements in the present work: firstly, there is an effort to arrange Bresson’s most important propositions based on his writings, interviews and films; secondly, we identify and organize Bresson’s appearances in Deleuze’s work, focusing on the issues related to image and sound in the cinematography; thirdly, there is an analysis of the role of the bressonian models in the modern cinema; finally, we apply the previously studied concepts to the film Au Hasard, Balthazar. Through this investigation, we seek to stress the importance of Robert Bresson’s body of work not only to the modern cinema, but also to the development of a cinema thought.